FAKTOR – FAKTOR YANG MEMPENGARUHI IPO UNDERPRICING DENGAN OWNERSHIP STRUCTURE SEBAGAI VARIABEL MODERASI - Giovanna Natasha, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to examine the influence of, firm internationalization and intellectual capital disclosure to IPO underpricing with ownership structure as the moderator variable on the companies listed on Indonesia Stock Exchange for the period 2009-2018. The sample was selected by using purposive sampling method and there are 36 companies that were selected as sample. This research uses multiple regression as the data analysis that being helped by Eviews 10.0. The result of this research shows that firm internationalization has no influenceto underpricing, while intellectual capital disclosure has negative and significant effect on underpricing. However, this study shows that firm internationalization which being moderated by ownership structure does not have a significant effect on underpricing.